Alien Encounters Popular Culture in Asian America - Shinn, Christopher A.; Indigo, Som; Kee, Joan; Fellezs, Kevin; Manalansan, Martin F. IV. 1960-; Nguyen, Mimi Thi 1974-; Nguyen, Mimi Thi 1974-; Lieu, Nhi T.; Wang, Oliver; Rodriguez, Robyn Magalit; Sandhu, Sukhdev; Maira, Sunaina 1969-; et al. (Duke University Press, 2007)
Alien Encounters showcases innovative directions in Asian American cultural studies. In essays exploring topics ranging from pulp fiction to multimedia art to import-car subcultures, contributors analyze Asian Americans' interactions with popular culture as both creators and consumers. Written by a new generation of cultural critics, these essays reflect post-1965 Asian America; the contributors pay nuanced attention to issues of gender, sexuality, transnationality, and citizenship, and they unabashedly take pleasure in pop culture.This interdisciplinary collection brings together contributors working in Asian American studies, English, anthropology, sociology, and art history. They consider issues of cultural authenticity raised by Asian American participation in hip hop and jazz, the emergence of an orientalist "Indo-chic" in U.S. youth culture, and the circulation of Vietnamese music variety shows. They examine the relationship between Chinese restaurants and American culture, issues of sexuality and race brought to the fore in the video performance art of a Bruce Lee-channeling drag king, and immigrant television viewers' dismayed reactions to a Chinese American chef who is "not Chinese enough." The essays in Alien Encounters demonstrate the importance of scholarly engagement with popular culture. Taking popular culture seriously reveals how people imagine and express their affective relationships to history, identity, and belonging.Contributors. Wendy Hui Kyong Chun, Kevin Fellezs, Vernadette Vicuña Gonzalez, Joan Kee, Nhi T. Lieu, Sunaina Maira, Martin F. Manalansan IV, Mimi Thi Nguyen, Robyn Magalit Rodriguez, Sukhdev Sandhu, Christopher A. Shinn, Indigo Som, Thuy Linh Nguyen Tu, Oliver Wang
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Nov 2020)
Keywords: SOCIAL SCIENCE / Ethnic Studies / Asian American Studies; Asian Americans -- Ethnic identity; Asian Americans -- Intellectual life; Asian Americans -- Social life and customs; Asian Americans -- Study and teaching; Popular culture -- United States